A study of radiative double electron capture in bare chromium ions at the ESR - Winters, Natalya; Warczak, A.; Tanis, J. A.; Gassner, T.; Gumberidze, A.; Hagmann, S.; Hillenbrand, P. M.; Kozhuharov, C.; Petridis, N.; Reuschl, R.; Schwemlein, Max; Sierpowski, D.; et al. (Physica scripta, 2013)
Radiative double electron capture is a fundamental atomic process which should be observed in collisions of bare ions with atoms, albeit with a much smaller cross-section than single radiative electron capture. A new experiment - to observe this rare process under single-collision conditions - has been performed at the internal gas jet target of the experimental storage ring at GSI in Darmstadt. X-ray spectra associated with single and double charge exchange have been observed in 30 MeV u−1 collisions of bare chromium ions (Cr24+) with helium and nitrogen target gases.
Gesehen am 16.11.2021